2005
DOI: 10.1161/01.hyp.0000154678.64340.7f
|View full text |Cite
|
Sign up to set email alerts
|

Locating a Blood Pressure Quantitative Trait Locus Within 117 kb on the Rat Genome

Abstract: Abstract-Previously, a blood pressure (BP) quantitative trait locus (QTL) on rat chromosome 9 (RNO9) was localized to a Ͻ2.4 cM interval using congenic strains generated by introgressing segments of RNO9 from the Dahl salt-resistant (R) rat into the background of the Dahl salt-sensitive (S) rat. Renal gene expression using Affymetrix gene chips was profiled on S and a congenic strain spanning the 2.4-cM BP QTL interval. This analysis identified 20 differentially expressed genes/expressed sequence tags. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
1
30
3
Order By: Relevance
“…3,4 (2) Resp18 and IA-2 may possess an additive effect on BP. This speculation is contrary to the data provided in our report, 1 wherein we have demonstrated that the effects of the QTL gene within the 117-kb region and that of Resp18 are not additive. 1 The amino acid substitution of Resp18 is correct in our report (ie, the sequence variation is from Isoleucine [Ile] to Valine [Val]).…”
Section: Responsecontrasting
confidence: 99%
See 2 more Smart Citations
“…3,4 (2) Resp18 and IA-2 may possess an additive effect on BP. This speculation is contrary to the data provided in our report, 1 wherein we have demonstrated that the effects of the QTL gene within the 117-kb region and that of Resp18 are not additive. 1 The amino acid substitution of Resp18 is correct in our report (ie, the sequence variation is from Isoleucine [Ile] to Valine [Val]).…”
Section: Responsecontrasting
confidence: 99%
“…This speculation is contrary to the data provided in our report, 1 wherein we have demonstrated that the effects of the QTL gene within the 117-kb region and that of Resp18 are not additive. 1 The amino acid substitution of Resp18 is correct in our report (ie, the sequence variation is from Isoleucine [Ile] to Valine [Val]). However, there is a discrepancy in the location of nucleotide coding for this amino acid substitution.…”
Section: Responsecontrasting
confidence: 99%
See 1 more Smart Citation
“…Attempts to identify BP QTLs by gene profiling again proved to be disappointing in experiments based on the comparison of renal gene expression of congenic and DSS strains. In these cases, differentially expressed candidates fell outside the precisely defined QTL intervals in the congenic strains (Moujahidine et al, 2004;Garrett et al, 2005). Thus, they could not be the QTLs in question.…”
Section: Use Of Heterozygotes As a Deductive Functional Test Of Qtlsmentioning
confidence: 99%
“…The search for differential gene expression has recently received considerable attention as a means of finding candidate genes for QTLs (Liang et al, 2003;McBride et al, 2003;Moujahidine et al, 2004;Garrett et al, 2005;Hubner et al, 2005;Yagil et al, 2005). It is easy to understand the tantalizing appeal of such an approach, because it generates gene candidates directly, rapidly and immediately, with apparent performance differentials.…”
Section: Use Of Heterozygotes As a Deductive Functional Test Of Qtlsmentioning
confidence: 99%